Oncological outcomes of rectal cancer patients with anastomotic leakage: A multicenter case-control study - Peltrini, Roberto; Carannante, Filippo; Costa, Gianluca; Bianco, Gianfranco; Garbarino, Giovanni Maria; Canali, Giulia; Mercantini, Paolo; Bracale, Umberto; Corcione, Francesco; Caricato, Marco; Capolupo, Gabriella Teresa (Frontiers in Surgery, 2022)
Introduction This study aimed to evaluate the impact of anastomotic leakage (AL) on oncological outcomes after restorative rectal cancer surgery. Methods Patients who underwent anterior resection for rectal adenocarcinoma between January 2011 and December 2017 were retrospectively reviewed. Data were collected from three colorectal surgery centers. Patients with grade B and C leaks according to the International Study Group of Rectal Cancer classification were identified and compared with the control group. Estimated recurrence and survival rates were compared using the log-rank method and Cox regression analysis. Results A total of 367 patients were included in the study, with a mean follow-up of 59.21 months. AL occurred in 64 patients (17.4%). Fifteen patients with AL (23.5%) developed local recurrence (LR) compared to 17 (4.8%) in the control group (p < 0.001). However, distant recurrence rates were similar (10.9% vs. 9.6%; p = 0.914) between the groups. Kaplan-Meier curves showed that patients with AL had a reduced 5-years local recurrence-free survival (96% vs. 78%, log-rank p < 0.001). AL (OR 4.576; 95% CI, 2.046–10.237; p < 0.001) and node involvement (OR 2.911; 95% CI, 1.240–6.835; p = 0.014) were significantly associated with LR in multivariate analysis. AL was significantly associated with DFS only at univariate analysis (HR 1.654; 95% CI: 1.024–2.672; p = 0.037), with a difference between 5-year DFS of patients with and without AL (71.6% vs. 86.4%, log-rank p = 0.04). Only male gender, pT3-4 stage, and node involvement were identified as independent prognostic factors for reduced DFS in the multivariate Cox regression analysis. Conclusion In this cohort of patients, AL was associated with a significant risk of LR after rectal cancer surgery.